AKUNTABILITAS MANAJEMEN DAN LAPORAN KEUANGAN ZAKAT MELALUI PENDEKATAN MODIFIKASI ACTION RESEARCH - Nikmatuniayah Nikmatuniayah; Lardin Korawijayanti; Siti Arbainah; Rikawati Rikawati; Muhammad Rois (Jurnal Riset Akuntansi Politala, 2023)
This study aims to prove the management accountability and financial reports of Amil Zakat Institutions in the Central Java region. This study used a descriptive qualitative approach with a modified action research method. Data collection was carried out through observation and interviews with the accounting & management department of Lazis, in the Central Java region. The selected and responding samples were Lazis Baiturrahman, Lazisnu Central Java, Dompet Sejuta Harapan, and IZI Central Java. The research model developed using a modified Participation Action Research (PAR) or Action Research. The results show that the problem is related to human resource capacity, zakat governance and a number of operational costs, as well as a limited marketing strategy. Distribution relates to a lack of resources and funding. The presentation of financial statements audited by external and sharia auditors.